Cardiotonic Steroids Induce Vascular Fibrosis Via Pressure-Independent Mechanism in NaCl-Loaded Diabetic Rats. Issue 5 (November 2019) - Fedorova, Olga V.; Fadeev, Artem V.; Grigorova, Yulia N.; Marshall, Courtney A.; Zernetkina, Valentina; Kolodkin, Nikolai I.; Agalakova, Natalia I.; Konradi, Alexandra O.; Lakatta, Edward G.; Bagrov, Alexei Y.
Abstract : Abstract: Endogenous cardiotonic steroid, marinobufagenin (MBG), induces Fli1-dependent tissue fibrosis. We hypothesized that an increase in MBG initiates the development of aortic fibrosis in salt-loaded rats with type 2 diabetes mellitus (DM2) via pressure-independent mechanism. DM2 was induced by a single intraperitoneal administration of 65 mg/kg streptozotocin to neonatal (4–5 days) male Wistar rats. Eight-week-old DM2 rats received water or 1.8% NaCl (DM-NaCl) solution for 4 weeks (n = 16); half of DM-NaCl rats were treated with anti-MBG monoclonal antibody (mAb) (DM-NaCl-AB) during week 4 of salt loading; control intact rats received water (n = 8/group). Blood pressure, MBG, erythrocyte Na/K-ATPase activity, aortic weights, levels of fibrosis markers (Fli1, protein kinase Cδ, transforming growth factor-β1, receptors of the transforming growth factor beta5, fibronectin, collagen-1), and sensitivity of the aortic explants to the vasorelaxant effect of sodium nitroprusside were assessed. No changes in systolic blood pressure were observed while erythrocyte Na/K-ATPase was inhibited by 30%, plasma MBG was doubled, and aortic markers of fibrosis became elevated in DM-NaCl rats versus control. Treatment of DM-NaCl rats with anti-MBG mAb activated Na/K-ATPase, prevented increases in aortic weights, and the levels of fibrosis markers returned to the control levels. The responsiveness of the aortic rings from DM-NaCl rats to the relaxant effect of sodium nitroprusside was reduced (half maximal effective concentration (EC50 ) = 29 nmol/L) versus control rings (EC50 = 7 nmol/L) and was restored by anti-MBG mAb (EC50 = 9 nmol/L). Our results suggest that in salt-loaded diabetic rats, MBG stimulates aortic collagen synthesis in a pressure-independent fashion and that 2 profibrotic mechanisms, Fli1 dependent and transforming growth factor-β dependent, underlie its effects.